Assessment of Academic Engagement and Grit: Strengths of Character to Be Developed in Postgraduate Students - Daura, Florencia Teresita (2020)
This paper introduces the results of an ongoing study, aimed at describing Academic Engagement and Grit standards in students attending postgraduate studies. To comply this a quantitative, descriptive and correlational study was applied to a convenience sample of 188 students who filled out the UWES-SS and the Grit Scale. The results showed that women scored better in the Academic Engagement dimensions and the Consistence of Interest factor in the Grit Scale. In addition, significant, positive correlations were found in both constructs. Conversely, no significant differences were found among postgraduate programs, nor among global Academic Engagement and global Grit by program or weekly study time. These findings showed the relevance of guiding students with specific strategies.